Cine EPID evaluation of two non‐commercial techniques for DIBH. Issue 2 (30th January 2014) - Jensen, Christopher; Urribarri, Jaime; Cail, Daniel; Rottmann, Joerg; Mishra, Pankaj; Lingos, Tatiana; Niedermayr, Thomas; Berbeco, Ross
Abstract : Purpose: : To evaluate the efficacy of two noncommercial techniques for deep inspiration breathhold (DIBH) treatment of left‐sided breast cancer (LSBC) using cine electronic portal imaging device (EPID) images. Methods: : 23 875 EPID images of 65 patients treated for LSBC at two different cancer treatment centers were retrieved. At the Milford Regional Cancer Center, DIBH stability was maintained by visual alignment of inroom lasers and patient skin tattoos (TAT). At the South Shore Hospital, a distance‐measuring laser device (RTSSD) was implemented. For both centers, cine EPID images were acquired at least once per week during beam‐on. Chest wall position relative to image boundary was measured and tracked over the course of treatment for every patient and treatment fraction for which data were acquired. Results: : Median intrabeam chest motion was 0.31 mm for the TAT method and 0.37 mm for the RTSSD method. The maximum excursions exceeded our treatment protocol threshold of 3 mm in 0.3% of cases (TAT) and 1.2% of cases (RTSSD). The authors did not observe a clinically significant difference between the two datasets. Conclusions: : Both noncommercial techniques for monitoring the DIBH location provided DIBH stability within the predetermined treatment protocol parameters (<3 mm). The intreatment imaging offered by the EPID operating in cine mode facilitates retrospective analysis and validation of both techniques.